Effect of spray‐dried cluster bean seed protein extract on the gel properties of single washed Nile tilapia surimi. Issue 11 (10th September 2022) - Priyadarshini, M. Bhargavi; Balange, Amjad; Xavier, Martin; Nayak, Binaya Bhusan
Abstract: The effect of incorporation of spray‐dried cluster bean seed protein extract (S‐CBPE) at 0.2, 0.4, 0.6, 0.8, and 1.0 g S‐CBPE/100 g of surimi was studied. The study is the first report on qualitative analysis and amino acid profiling of S‐CBPE using HPLC ‐QTOF ‐MS2 . A total of 10 amino acids were identified. The outcome exhibited that S‐CBPE addition at a level of 0.4%–0.8% improved gel strength. The presence of arginine, histidine, and lysine in the extract might have contributed to the gel‐forming ability. The disappearance of Tmax1 was observed at the incorporation of 0.6% (T‐3p). FTIR analysis revealed the hydrophobic interactions and the formation of disulfide linkages that occurred between the myofibrillar protein of surimi and S‐CBPE. Hence, the spray‐dried extract can be a novel compound to improve the properties of low gel strength surimi at an optimized ratio. Novelty impact statement: The present study is the first report on the utilization of cluster bean seed extract to enhance the gel strength of surimi. The presence of novel bioactive peptides was identified using HPLC‐QTOF‐MS/MS. Enhanced the gel strength of the freshwater surimi grade from AA (>600 g cm) to SSA (>1000 g cm).